Enhancing DVNN-WCSM Technique for Double-Valued Neutrosophic Multiple-Attribute Decision-Making in Digital Economy: A Case Study on Enhancing the Quality of Development of Henan's Cultural and Tourism Industry - Yourong Guo (Neutrosophic Sets and Systems)
Henan Province is the core area of the Yellow River Basin and an important area for inheritance of Yellow River culture. Promoting the development of the cultural and tourism industry in Henan Province essentially involves integrating the cultural resources of the Yellow River in Henan Province, creating cultural tourism products and projects with the cultural characteristics of the Yellow River region, thereby enriching the content of Henan's tourism industry and promoting its economic development. In the future development of the cultural and tourism industry, Henan Province not only needs to solve current problems of insufficient industrial competitiveness, lack of product innovation, and incomplete brand shaping, but also needs to pay attention to the economic and social benefits of the cultural and tourism industry. Only in this way could we truly achieve the high-quality development goals of the cultural and tourism industry. The high-quality development quality evaluation of Henan's cultural and tourism industry driven by digital economy is multiple-attribute decision-making (MADM). The cosine similarity measure (CSM) has been put forward MADM. The double-valued neutrosophic sets (DVNSs) are put forward characterizing fuzzy information during the high quality development quality evaluation of Henan's cultural and tourism industry driven by digital economy. In this study, the double-valued neutrosophic number CSM (DVNN-CSM) technique and double-valued neutrosophic number weighted CSM (DVNN-WCSM) technique are put forward the MADM along with DVNSs. Finally, a numerical study for high-quality development quality evaluation of Henan’s cultural and tourism industry driven by digital economy is put forward validating the DVNNN-WCSM.